Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1111/j.1447-0756.2001.tb01250.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of Pregnancy with Congenital Antithrombin III Deficiency: Two Case Reports and a Review of the Literature

Abstract: Women with antithrombin (AT) I11 deficiency are prone to pregnancy-associated venous thromboembolism. We report 2 cases with genetically confirmed ATIII deficiency, one with a mutation in exon 3A and the other with an exon 4 deletion, in whom the pregnancies were successfully managed with prophylactic therapies for thrombosis. A 35-year-old pregnant woman was treated with intravenous infusions of ATIII concentrate alone, and the other 22-year-old pregnant woman was mainly treated with subcutaneous injections o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…43 Women with antithrombin deficiency are prone to pregnancy-associated venous thromboembolism. 44 Severe deficiencies in protein C and protein S result in purpura fulminans, venous thrombosis, and/or pulmonary embolism in the newborn. To date, there are no reports of humans deficient in TFPI.…”
Section: Role Of the Different Anticoagulant Pathways In Tissue-specimentioning
confidence: 99%
“…43 Women with antithrombin deficiency are prone to pregnancy-associated venous thromboembolism. 44 Severe deficiencies in protein C and protein S result in purpura fulminans, venous thrombosis, and/or pulmonary embolism in the newborn. To date, there are no reports of humans deficient in TFPI.…”
Section: Role Of the Different Anticoagulant Pathways In Tissue-specimentioning
confidence: 99%
“…Samson et al 14 gave AT concentrate for the preparation of the delivery and shortly after delivery, while DeStefano et al 15 gave only one dose of AT concentrate after delivery. Yamada et al 16 showed a case of two pregnant women: a 35-year old pregnant patient was given only AT concentrate during pregnancy, while a 22-year old pregnant patient was given only LMWH in prophylactic doses and low doses of aspirin.…”
Section: Discussionmentioning
confidence: 98%
“…This clinical case report suggests that the surgeon has to appreciate that ATIIID is a very rare phenomenon, especially in pregnant women after cardiac surgery, and correct management should be started as soon as possible to avoid a serious outcome. The first inherited case of ATD was diagnosed in 1965 as a thrombophilia state, but then no case of ATIIID was reported in postcardiac surgery in pregnant woman (15,16).…”
Section: Discussionmentioning
confidence: 99%